Model of the Cultural Da’wah of the Sunan Gunung Jati and its Relevance with the Current Da’wah of Islam - Hanif Cahyo Adi Kistoro (Religia, 2021)
The purpose of this research is to explain the model of the pre-culture that is carried out by Sunan Gunung Jati. This type of research is library research (library research). The main data sources of this study are books, journals, and other works as the main literature. Data analysis techniques use content analysis techniques by conducting source criticism, interpretation, and historiography. From the results of the study, it was concluded that the cultural propaganda model of Sunan Gunung Jati in the dissemination of Islamic teachings through petitah-petitih, authority, and ipat-ipit and magersari. The relevance of advice in petitih petitih and authority and ipat ipit is to facilitate the teachings of Islam following the cultural understanding of the community. While magersari is an implementation of the value of Islamic teachings in social interaction or muamalah.